Prefrontal and anterior cingulate cortex neurons encode attentional targets even when they do not apparently bias behavior - Westendorff, Stephanie; Kaping, Daniel; Everling, Stefan; Womelsdorf, Thilo (Journal of neurophysiology, 2016)
Neurons in anterior cingulate and prefrontal cortex (ACC/PFC) carry information about behaviorally relevant target stimuli. This information is believed to affect behavior by exerting a top-down attentional bias on stimulus selection. However, attention information may not necessarily be a biasing signal but could be a corollary signal that is not directly related to ongoing behavioral success, or it could reflect the monitoring of targets similar to an eligibility trace useful for later attentional adjustment. To test this suggestion we quantified how attention information relates to behavioral success in neurons recorded in multiple subfields in macaque ACC/PFC during a cued attention task. We found that attention cues activated three separable neuronal groups that encoded spatial attention information but were differently linked to behavioral success. A first group encoded attention targets on correct and error trials. This group spread across ACC/PFC and represented targets transiently after cue onset, irrespective of behavior. A second group encoded attention targets on correct trials only, closely predicting behavior. These neurons were not only prevalent in lateral prefrontal but also in anterior cingulate cortex. A third group encoded target locations only on error trials. This group was evident in ACC and PFC and was activated in error trials "as if" attention was shifted to the target location but without evidence for such behavior. These results show that only a portion of neuronaly available information about attention targets biases behavior. We speculate that additionally a unique neural subnetwork encodes counterfactual attention information.
Keywords: reakční čas; Prefrontal Cortex; podněty; Analysis of Variance; Male; Photic Stimulation; Attention; Gyrus Cinguli; cingulární gyrus; výběrové chování; zkreslení výsledků (epidemiologie); Choice Behavior; prefrontální mozková kůra; Reaction Time; mužské pohlaví; neurony; pozornost; Cues; Time Factors; Macaca mulatta; Animals; akční potenciály; Action Potentials; Space Perception; analýza rozptylu; zvířata; Bias; Neurons; časové faktory; vnímání prostoru; světelná stimulace